Literary translator studies - Kaindl, Klaus; Kolb, Waltraud, 1962-; Schlager, Daniela (Benjamins translation library,, 2021)
"This volume extends and deepens our understanding of Translator Studies by charting new territory in terms of theory, methods and concepts. The focus is on literary translators, their roles, identities, and personalities. The book introduces pertinent translator-centered approaches in four sections: historical-biographical studies, social-scientific and process-oriented methods and approaches that use paratexts or translations to study literary translators. Drawing on a variety of concepts, such as identity, role, self, posture, habitus, and voice, the various chapters showcase forgotten literary translators and shed new light on some well-known figures; they examine literary translators not as functioning units but as human beings in their uniqueness. Literary Translator Studies as a subdiscipline of Translation Studies demonstrates how exploring the cultural, social, psychological, and cognitive facets of translatorial subjects contributes to a holistic understanding of translation"--